Factors Related To The Success Of Exclusive Breastfeeding In Infants Aged 0–6 Months - Lumastari Ajeng Wijayanti; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Exclusive breastfeeding refers to feeding infants only breast milk for the first six months of life without additional food or drink , except medicines , vitamins , or minerals when medically indicated . Despite its benefits , the coverage of exclusive breastfeeding in Indonesia remains below the national targets. Maternal knowledge , occupation , husband's support , health worker support , and early initiation of breastfeeding are among the factors influencing breastfeeding success. To analyze factors associated with the success of exclusive breastfeeding among infants aged 0–6 months. This study employed an analytical observational design with a cross-sectional approaches. A total of 120 mothers with infants aged 6–12 months were selected using purposive sampling. Data were collected using structured questionnaires and analyzed using the Chi- square test with a significance level of 0.05. The proportion of mothers who successfully practiced exclusive breastfeeding was 65.8%. Maternal knowledge , occupation , husband's support , health worker support , and early initiation of breastfeeding was significantly associated with exclusive breastfeeding success (p<0.05). Maternal knowledge , occupation , husband's support , health worker support , and early initiation of breastfeeding are significantly associated with successful exclusive breastfeeding